STUDI KEPUSTAKAAN MENGENAI LANDASAN TEORI BODY IMAGE BAGI PERKEMBANGAN REMAJA - Riskha Ramanda; Zarina Akbar; R. A. Murti Kusuma Wirasti (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2019)
This study aims to describe the theoretical basis of body image for adolescent development. The research method used is the library research method. The data collection method used is the documentation method. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent misinformation in data analysis, checks are carried out between libraries and reread the library. The purpose of this study was to develop a theoretical basis for body image in adolescents. The results of this study are the compilation of a study of body image for the development of adolescents as a whole, including: 1) understanding body image, 2) body image components, 3) aspects in body image, 4) factors that influence body image, 5) body image for adolescent development.